Isotopically Labeled Desthiobiotin Azide (isoDTB) Tags Enable Global Profiling of the Bacterial Cysteinome. Issue 7 (7th January 2020) - Zanon, Patrick R. A.; Lewald, Lisa; Hacker, Stephan M.
Abstract: Rapid development of bacterial resistance has led to an urgent need to find new druggable targets for antibiotics. In this context, residue‐specific chemoproteomic approaches enable proteome‐wide identification of binding sites for covalent inhibitors. Described here are easily synthesized isotopically labeled desthiobiotin azide (isoDTB) tags that shortened the chemoproteomic workflow and allowed an increased coverage of cysteines in bacterial systems. They were used to quantify 59 % of all cysteines in essential proteins in Staphylococcus aureus and enabled the discovery of 88 cysteines that showed high reactivity, which correlates with functional importance. Furthermore, 268 cysteines that are engaged by covalent ligands were identified. Inhibition of HMG‐CoA synthase was verified and will allow addressing the bacterial mevalonate pathway through a new target. Overall, a broad map of the bacterial cysteinome was obtained, which will facilitate the development of antibiotics with novel modes‐of‐action. Abstract : On target : Isotopically labeled desthiobiotin azide (isoDTB) tags were synthesized in a straightforward manner and allowed residue‐specific profiling of the cysteinome in S. aureus . In this way, 268 cysteines that can be engaged by covalent ligands were identified. These cysteines are targets for the development of antibiotics with novel modes‐of‐action.